Review of new insights into antimicrobial agents - Dehghan Esmatabadi, M. J.; Bozorgmehr, A.; Hajjari, S. N.; Sadat Sombolestani, A.; Malekshahi, Z. V.; Sadeghizadeh, M. (Cellular and Molecular Biology, 2017)
People have known the bacteria and have used various ways to deal with them, from a long time ago. Perhaps, natural antibiotics with have been the first step in fighting against pathogens. However, several factors, such as dealing with unfamiliar bacteria or emergence of drug-resistant species, have motivated us to discover new antibiotics or  even change previous types. In this regard, a variety of natural and synthetic antibiotics with different origins, mechanism of action, structures and functional spectrum, have been developed and used. Some impact on the synthesis of nucleic acids and some affect protein synthesis so destroy bacteria. There is a ring in the structure of most of the antibiotics which gives them special properties. However, despite their numerous advantages, antibiotics also have drawbacks ehich limit their use in all situations. Therefore, other approaches such as photodynamic therapy (PDT) and antibacterial peptides were considered as alternatives. Photodynamic therapy (PDT) is a treatment that uses photosensitizing agents, along with light, to kill bacteria. The photosensitizing agents only work after they have been activated by certain kinds of light. Antibacterial peptides are a unique and diverse group of molecules which have  between 12 and 50 amino acids in general.  In this paper, will reviewt hree mentioned topics, namely antibiotics, photodynamic therapy and antibacterial peptides and will discuss the advantages and disadvantages of each approach briefly.